A sodium ion battery positive electrode precursor material, positive electrode material and preparation method
The positive electrode precursor material of sodium ion battery prepared by co-precipitation method achieves uniform doping of iron, titanium and lithium elements by regulating the particle size and stoichiometric ratio, solving the problems of low cyclic stability and capacity density of the positive electrode materials in the prior art, and improving the performance and production cost-effectiveness of the material.
Patent Information
- Application Number
- CN202311280212.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-07
- Publication Date
- 2025-04-08
AI Technical Summary
During the synthesis process, the existing sodium ion battery layered oxide positive electrode materials have uneven distribution of doping elements and large particle size distribution width, resulting in low cyclic stability and capacity density.
Mn0.6-a-bFeaTibNi0.4-cLicCO3, a positive electrode precursor material of sodium ion battery, was prepared by co-precipitation method, and the particle size, particle size distribution width and stoichiometric ratio of each component were regulated, so as to achieve uniform doping of iron, titanium and lithium elements, and inhibit complex phase change and side reactions of layered oxides.
The cycle stability and capacity density of the cathode material are improved, and the production cost is reduced, making the cathode material of sodium ion battery easy to be produced on a large scale.
Smart Images

Figure CN119786594A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a sodium ion battery positive electrode precursor material, a positive electrode material and a preparation method. Background Art
[0002] With the rapid development of social economy, various types of electrical equipment are becoming more and more popular, and people's demand for secondary batteries is also increasing. Therefore, the development of new energy technology has become the focus of people's increasing attention. At present, lithium-ion batteries have become the mainstream energy storage devices due to their advantages such as high capacity and long service life, and have been widely used in the fields of electronic consumption, energy storage and electric vehicles.
[0003] However, due to the scarcity of lithium resources, the production capacity of lithium-ion batteries cannot meet the existing market demand. The sodium-ion battery system has similar physical and chemical properties to lithium batteries, and is rich in resources, low in price, and has excellent electrochemical properties, providing a new choice for electrochemical energy storage, especially large-scale energy storage. Among them, sodium-ion layered oxide cathode materials have received increasing attention due to their advantages such as high redox potential, high specific capacity, and low price.
[0004] However, in the prior art, there are still many problems in the synthesis process of layered oxide positive electrode materials, such as uneven distribution of doping elements and wide particle size distribution, which in turn lead to low cycle stability and capacity density of the positive electrode materials. Summary of the invention
[0005] The purpose of this application is to provide a sodium ion battery positive electrode precursor material, a positive electrode material and a preparation method, so that the sodium ion battery positive electrode material has higher cycle stability and better capacity density. The specific technical solution is as follows:
[0006] The first aspect of the present application provides a sodium ion battery positive electrode precursor material, the positive electrode precursor material has the chemical formula: Mn 0.6-a-b Fe a Ti b Ni 0.4-c Li c CO 3, 0.1≤a≤0.2, 0.03≤b≤0.15, 0.02≤c≤0.1, the volume average particle size Dv50 of the positive electrode precursor material is 3μm to 7μm, and the distribution width of the particle size K90≤0.9. The positive electrode precursor material of the sodium ion battery prepared by the coprecipitation method realizes the uniform doping of iron, titanium and lithium elements in the positive electrode material, and the synergistic co-doping of the three elements of iron, titanium and lithium at different sites in the transition metal layer of the positive electrode material inhibits the complex phase change of the layered oxide during the charge and discharge cycle, reduces the adverse effects of side reactions under high voltage, and makes the positive electrode material have good cycle stability and high capacity density.
[0007] In some embodiments of the present application, the tap density of the positive electrode precursor material is 1.3 g / cm 3 Up to 1.8g / cm 3 , with a specific surface area of 15m 2 / g to 30m 2 / g. By regulating the tap density and specific surface area of the positive electrode precursor material within the above range, the positive electrode material has sufficient active surface, which is conducive to the embedding and extraction of sodium ions in the positive electrode material, thereby achieving better capacity and rate performance, and at the same time can reduce the side reaction between the positive electrode material and the electrolyte, thereby improving the cycle stability of the positive electrode material.
[0008] In some embodiments of the present application, the manganese source of the positive electrode precursor material is selected from at least one of manganese acetate, manganese nitrate or manganese sulfate. By selecting the above materials as the manganese source, it is beneficial to uniformly dope the manganese element into the positive electrode precursor material, thereby facilitating the generation of a uniform and stable positive electrode precursor material.
[0009] In some embodiments of the present application, the iron source of the positive electrode precursor material is selected from at least one of ferric chloride, ferric nitrate or ferric sulfate. By selecting the above materials as the iron source, it is beneficial to uniformly dope the iron element into the positive electrode precursor material, thereby facilitating the generation of a uniform and stable positive electrode precursor material; at the same time, the iron element can also stabilize the crystal structure of the positive electrode material, increase the ionic conductivity of the positive electrode material, and reduce the production cost of the positive electrode material for sodium ion batteries.
[0010] In some embodiments of the present application, the titanium source of the positive electrode precursor material is selected from at least one of titanium oxysulfate or titanium tetrachloride. By selecting the above materials as the titanium source, it is beneficial to uniformly dope the titanium element into the positive electrode precursor material, thereby facilitating the generation of a uniform and stable positive electrode precursor material; the titanium element can also reduce the degree of ion mixing, inhibit harmful phase changes during the charge and discharge process, and improve the structural stability of the positive electrode material.
[0011] In some embodiments of the present application, the nickel source of the positive electrode precursor material is selected from at least one of nickel acetate, nickel nitrate or nickel sulfate. By selecting the above materials as the nickel source, it is beneficial to uniformly dope the nickel element into the positive electrode precursor material, thereby facilitating the generation of a uniform and stable positive electrode precursor material, and also facilitating the improvement of the capacity density of the positive electrode material.
[0012] In some embodiments of the present application, the lithium source of the positive electrode precursor material is selected from at least one of lithium acetate, lithium hydroxide or lithium nitrate. By selecting the above materials as the lithium source, it is beneficial to uniformly dope lithium ions into the positive electrode precursor material, thereby facilitating the generation of uniform and stable positive electrode precursor materials, and also facilitating the improvement of the ion conductivity of the positive electrode material, smoothing the charge and discharge curve of the secondary battery, and improving the cycle performance of the secondary battery.
[0013] The second aspect of the present application provides a method for preparing a positive electrode precursor material, wherein the method comprises:
[0014] (1) According to the positive electrode precursor material Mn 0.6-a-b Fe a Ti b Ni 0.4-c Li c CO 3 The stoichiometric ratio of manganese, iron, titanium, nickel and lithium is: weigh manganese source, iron source, titanium source, nickel source and lithium source respectively and dissolve them in deionized water to prepare a mixed metal salt solution with a total concentration of manganese, iron, titanium, nickel and lithium of 1.2 mol / L to 2 mol / L, wherein 0.1≤a≤0.2, 0.03≤b≤0.15, and 0.02≤c≤0.1;
[0015] (2) adding deionized water as a base liquid into a coprecipitation reaction vessel, and then introducing nitrogen into the base liquid at a nitrogen flow rate of 20 mL / min to 50 mL / min, and then respectively adding a precipitant, a complexing agent and a mixed metal salt solution into the coprecipitation reaction vessel to perform a coprecipitation reaction, wherein during the coprecipitation reaction, the pH in the coprecipitation reaction vessel is controlled to be 7.5 to 9.5, the reaction temperature is 50° C. to 60° C., the stirring speed is 500 r / min to 800 r / min, the precipitant is a 1 mol / L sodium carbonate solution, and the complexing agent is a 0.5 mol / L ammonia solution;
[0016] (3) After the injection of the mixed metal salt solution in the coprecipitation reaction container is completed, the addition of the precipitant and the complexing agent is stopped, and then the stirring speed is continued at 200 r / min to 300 r / min, and the aging reaction is carried out for 6 h to 10 h, and then the obtained coprecipitation product is filtered and washed with deionized water, and then placed in a vacuum drying oven at 80° C. to 120° C. for 12 h to 24 h to obtain the positive electrode precursor material Mn0.6-a-b Fe a Ti b Ni 0.4-c Li c CO 3 By regulating the total concentration of the mixed metal salt solution of manganese, iron, titanium, nickel and lithium, the nitrogen flow rate, the coprecipitation reaction pH, the coprecipitation reaction temperature, the coprecipitation reaction stirring speed, the aging reaction time, the aging reaction stirring speed and the vacuum drying temperature and time within the above range, it is beneficial to the growth nucleation of the positive electrode precursor, generate a uniform and stable positive electrode precursor material, and then obtain a positive electrode material with uniform particle size distribution and uniform element doping.
[0017] The third aspect of the present application provides a positive electrode material comprising the positive electrode precursor material in any of the aforementioned embodiments, wherein the chemical formula of the positive electrode material is: Na x Mn 0.6-a-b Fe a Ti b Ni 0.4-c Li c O 2 , 0.85≤x≤1, 0.1≤a≤0.2, 0.03≤b≤0.15, 0.02≤c≤0.1, and the sodium source of the positive electrode material is selected from at least one of sodium carbonate, sodium bicarbonate or sodium nitrate. By regulating the stoichiometric number of the sodium element in the positive electrode material within the above range, the positive electrode material has a sufficiently high sodium content, which is also beneficial to the stability of the positive electrode material structure after the sodium ions are released, and the diffusion rate of the sodium ions is increased.
[0018] Beneficial effects of this application:
[0019] The present application provides a sodium ion battery positive electrode precursor material, a positive electrode material and a preparation method. The chemical formula of the positive electrode precursor material is: Mn 0.6-a-b Fe a Ti b Ni 0.4-c Li c CO 3, 0.1≤a≤0.2, 0.03≤b≤0.15, 0.02≤c≤0.1, the volume average particle size Dv50 of the positive electrode precursor material is 3μm to 7μm, and the particle size distribution width K90≤0.9. The present application discloses a sodium ion battery positive electrode precursor material prepared by a coprecipitation method. By regulating the particle size, particle size distribution width and stoichiometric ratio of the positive electrode precursor material, uniform doping of iron, titanium and lithium in the positive electrode material is achieved. The synergistic co-doping of the three elements of iron, titanium and lithium at different sites in the transition metal layer of the positive electrode material inhibits the complex phase transition of the layered oxide during the charge and discharge cycle, reduces the adverse effects of side reactions under high voltage, and enables the positive electrode material to have good cycle stability and high capacity density. By regulating the volume average particle size Dv50 of the positive electrode precursor material to be 3μm to 7μm and the particle size distribution width K90≤0.9, the particle size of the positive electrode material is relatively uniform, thereby achieving better cycle stability. The doping of the iron element also reduces the production cost of the positive electrode material, making the sodium ion battery positive electrode precursor material and the positive electrode material easy to mass produce.
[0020] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0022] Figure 1 This is a scanning electron microscope image of the positive electrode precursor material in Example 1 of the present application;
[0023] Figure 2 This is a scanning electron microscope image of the positive electrode precursor material in Comparative Example 2 of the present application;
[0024] Figure 3 This is a particle size test diagram of the positive electrode precursor material in Example 1 of the present application;
[0025] Figure 4 is the X-ray diffraction (XRD) pattern of the positive electrode precursor material in Example 1 of the present application;
[0026] Figure 5 The XRD spectrum of the positive electrode precursor material in Comparative Example 2 of the present application;
[0027] Figure 6 This is a scanning electron microscope image of the positive electrode material in Example 1 of the present application;
[0028] Figure 7 This is a scanning electron microscope image of the positive electrode material in Comparative Example 1 of the present application;
[0029] Figure 8 This is a charge and discharge curve diagram of the secondary battery in Example 1 of the present application at 0.1C and 2-4V for the first cycle;
[0030] Fig. 9 This is a charge and discharge curve diagram of the secondary battery in Example 1 of the present application at 0.1C and 2.2-4.4V for the first cycle. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application. The specific technical solutions are as follows:
[0032] The first aspect of the present application provides a sodium ion battery positive electrode precursor material, the positive electrode precursor material has the chemical formula: Mn 0.6-a-b Fe a Ti b Ni 0.4-c Li c CO 3 , 0.1≤a≤0.2, 0.03≤b≤0.15, 0.02≤c≤0.1, wherein the volume average particle size Dv50 of the positive electrode precursor material is 3μm to 7μm, and the particle size distribution width K90≤0.9. The present application discloses a sodium ion battery positive electrode precursor material prepared by a coprecipitation method. By regulating the particle size, particle size distribution width and stoichiometric ratio of the positive electrode precursor material, uniform doping of iron, titanium and lithium in the positive electrode material is achieved. The synergistic co-doping of the three elements at different sites in the transition metal layer of the positive electrode material inhibits the complex phase transition of the layered oxide during the charge and discharge cycle, reduces the adverse effects of side reactions under high voltage, and enables the positive electrode material to have good structural stability and high capacity density. By regulating the volume average particle size Dv50 of the positive electrode precursor material to be 3μm to 7μm and the particle size distribution width K90≤0.9, the particle size of the positive electrode material is relatively uniform, thereby achieving better cycle stability. The doping of the iron element also reduces the production cost of the positive electrode material, making the sodium ion battery positive electrode precursor material and the positive electrode material easy to mass produce.
[0033] In some embodiments of the present application, the tap density of the positive electrode precursor material is 1.3 g / cm 3 Up to 1.8g / cm 3, with a specific surface area of 15m 2 / g to 30m 2 / g. The tap density of the positive electrode precursor material will affect the capacity density of the positive electrode material. If the tap density is too large, it will hinder the embedding and extraction of sodium ions during the charge and discharge process, which is not conducive to high-rate charge and discharge; if the tap density is too small, it will reduce the capacity density of the positive electrode material. The specific surface area of the positive electrode precursor material will affect the cycle stability of the positive electrode material. If the specific surface area is too large, the side reaction between the positive electrode material and the electrolyte will increase, thereby reducing the cycle stability of the positive electrode material; if the specific surface area is too small, it is difficult for sodium ions to embed and extract, and the capacity of the positive electrode material is low and the rate performance is poor. The present application regulates the tap density and specific surface area of the positive electrode precursor material within the above range, so that the positive electrode material has sufficient active surface, which is conducive to the embedding and extraction of sodium ions in the positive electrode material, thereby achieving better capacity and rate performance, while reducing the side reaction between the positive electrode material and the electrolyte, thereby improving the cycle stability of the positive electrode material.
[0034] In some embodiments of the present application, the manganese source of the positive electrode precursor material is selected from at least one of manganese acetate, manganese nitrate or manganese sulfate. The present application adjusts the manganese source of the positive electrode precursor material to be selected from the above materials, which is conducive to uniform doping of manganese elements into the positive electrode precursor material, thereby facilitating the generation of a uniform and stable positive electrode precursor material.
[0035] In some embodiments of the present application, the iron source of the positive electrode precursor material is selected from at least one of ferric chloride, ferric nitrate or ferric sulfate. The present application adjusts the iron source of the positive electrode precursor material to be selected from the above materials, which is conducive to uniform doping of the iron element into the positive electrode precursor material, thereby facilitating the generation of a uniform and stable positive electrode precursor material; at the same time, the iron element can also stabilize the crystal structure of the positive electrode material, increase the ionic conductivity of the positive electrode material, and reduce the production cost of the positive electrode material for sodium ion batteries.
[0036] In some embodiments of the present application, the titanium source of the positive electrode precursor material is selected from at least one of titanium oxysulfate or titanium tetrachloride. The present application adjusts the titanium source of the positive electrode precursor material to be selected from the above materials, which is conducive to uniform doping of the titanium element into the positive electrode precursor material, thereby facilitating the generation of a uniform and stable positive electrode precursor material; the titanium element can also reduce the degree of ion mixing, inhibit harmful phase changes during charging and discharging, and improve the structural stability of the positive electrode material.
[0037] In some embodiments of the present application, the nickel source of the positive electrode precursor material is selected from at least one of nickel acetate, nickel nitrate or nickel sulfate. By selecting the above materials as the nickel source, it is beneficial to uniformly dope the nickel element into the positive electrode precursor material, thereby facilitating the generation of a uniform and stable positive electrode precursor material, and also facilitating the improvement of the capacity density of the positive electrode material.
[0038] In some embodiments of the present application, the lithium source of the positive electrode precursor material is selected from at least one of lithium acetate, lithium hydroxide or lithium nitrate. By selecting the above materials as the lithium source of the positive electrode precursor material, it is beneficial to uniformly dope lithium ions into the positive electrode precursor material, thereby facilitating the generation of uniform and stable positive electrode precursor materials; the uniform doping of lithium ions into the positive electrode precursor material is also beneficial to improving the ionic conductivity of the positive electrode material, smoothing the charge and discharge curve of the secondary battery, and improving the cycle performance of the secondary battery.
[0039] The second aspect of the present application provides a method for preparing a positive electrode precursor material for a sodium ion battery, the method comprising: (1) preparing a positive electrode precursor material Mn 0.6-a-b Fe a Ti b Ni 0.4-c Li c CO 3 The stoichiometric ratio of manganese, iron, titanium, nickel and lithium in the coprecipitation reaction vessel is adjusted, and the manganese source, iron source, titanium source, nickel source and lithium source are weighed and dissolved in deionized water to prepare a mixed metal salt solution with a total concentration of manganese, iron, titanium, nickel and lithium of 1.2 mol / L to 2 mol / L, wherein 0.1≤a≤0.2, 0.03≤b≤0.15, and 0.02≤c≤0.1; (2) deionized water is added to a coprecipitation reaction vessel as a base liquid, and then an inert gas is introduced into the base liquid at a flow rate of 20 mL / min to 50 mL / min, and then a precipitant, a complexing agent and the mixed metal salt solution are respectively added dropwise to the coprecipitation reaction vessel for a coprecipitation reaction, and in the coprecipitation reaction, During the precipitation reaction, the pH in the coprecipitation reaction container is controlled to be 7.5 to 9.5, the reaction temperature is 50° C. to 60° C., the stirring speed is 500 r / min to 800 r / min, the precipitant is 1 mol / L sodium carbonate solution, and the complexing agent is 0.5 mol / L ammonia solution; (3) after the injection of the mixed metal salt solution in the coprecipitation reaction container is completed, the dropwise addition of the precipitant and the complexing agent is stopped, and then the stirring is continued at a stirring speed of 200 r / min to 300 r / min, and the aging reaction is carried out for 6 h to 10 h, and then the obtained coprecipitation product is filtered and washed with deionized water, and then placed in a vacuum drying oven at 80° C. to 120° C. for 12 h to 24 h to obtain the positive electrode precursor material Mn 0.6-a-b Fe a Ti b Ni 0.4-c Li c CO 3. The present application prepares the positive electrode precursor material by the above-mentioned coprecipitation method, and realizes the uniform doping of iron, titanium and lithium in the positive electrode material by regulating the stoichiometric ratio of each component of the positive electrode precursor material. The synergistic co-doping of the three elements at different sites in the transition metal layer of the positive electrode material inhibits the complex phase change of the layered oxide during the charge and discharge cycle, reduces the adverse effects of the side reactions under high voltage, and makes the positive electrode material have good structural stability and high capacity density; the doping of iron element also reduces the production cost of the positive electrode material, making the positive electrode precursor material and the positive electrode material of the sodium ion battery easy to mass produce, and has obvious cost advantages. At the same time, the present application regulates the total concentration of the mixed metal salt solution of manganese, iron, titanium, nickel and lithium, the nitrogen flow rate, the coprecipitation reaction pH, the coprecipitation reaction temperature, the coprecipitation reaction stirring speed, the aging reaction time, the aging reaction stirring speed and the vacuum drying temperature and time within the above range, which is conducive to the growth and nucleation of the positive electrode precursor, generates a uniform and stable positive electrode precursor material, and then obtains a positive electrode material with uniform particle size distribution and uniform element doping.
[0040] The third aspect of the present application provides a positive electrode material comprising the positive electrode precursor material of a sodium ion battery according to any of the aforementioned embodiments, wherein the chemical formula of the positive electrode material is: Na x Mn 0.6-a-b Fe a Ti b Ni 0.4-c Li c O 2 , 0.85≤x≤1, 0.1≤a≤0.2, 0.03≤b≤0.15, 0.02≤c≤0.1, the sodium source of the positive electrode material is selected from at least one of sodium carbonate, sodium bicarbonate or sodium nitrate. The present application uses the above materials as the sodium source of the positive electrode material, which is conducive to the uniform diffusion of sodium ions in the layered structure of the positive electrode material to form a sodium ion layer, thereby obtaining a positive electrode material with higher cycle stability and higher capacity density; by regulating the stoichiometric number of the sodium element in the positive electrode material within the above range, the positive electrode material has a sufficiently high sodium content, which is also conducive to the stability of the positive electrode material structure after the sodium ions are released, and increases the diffusion rate of the sodium ions.
[0041] The present application has no particular restrictions on the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the positive electrode sheet may include a positive electrode material layer and a positive electrode current collector. The positive electrode material layer of the present application may also include a conductive agent and a binder. The conductive agent includes at least one of conductive carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, nanocarbon fibers or graphene. The binder includes at least one of polyvinylidene fluoride, sodium polyacrylate, polyvinyl pyrrolidone, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer or polypropylene. The present application has no particular restrictions on the mass ratio of the positive electrode material, conductive agent and binder in the positive electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, the mass ratio of the positive electrode material, conductive agent and binder in the positive electrode material layer is (70-95): (5-10): (5-10).
[0042] The present application has no special restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the positive electrode current collector may include aluminum foil, aluminum alloy foil or a composite current collector, etc. The present application has no special restrictions on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5μm to 20μm. In the present application, the positive electrode active material layer can be arranged on one surface in the thickness direction of the positive electrode current collector, or on two surfaces in the thickness direction of the positive electrode current collector. It should be noted that the "surface" here can be the entire area of the positive electrode current collector or a partial area of the positive electrode current collector. The present application has no special restrictions, as long as the purpose of the present application can be achieved.
[0043] The present application has no particular restrictions on the preparation method of the positive electrode sheet, and a preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the positive electrode sheet includes but is not limited to the following steps: dispersing the active material, the conductive agent and the binder in N-methylpyrrolidone (NMP) solvent to form a uniform positive electrode slurry, coating the positive electrode slurry on the positive electrode collector, drying, cold pressing, cutting, slitting and re-drying to obtain a positive electrode sheet.
[0044] The present application has no particular restrictions on the separator, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved. For example, the material of the separator can include but is not limited to at least one of polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polyimide (PI) or glass fiber; the type of the separator can include but is not limited to at least one of dry film, microporous film, composite film, rolled film or spun film.
[0045] The present application has no particular restrictions on the electrolyte, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, at least one of ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate (VC) or fluoroethylene carbonate (FEC) is mixed in a certain mass ratio to obtain a non-aqueous organic solvent, and then sodium salt is added to dissolve and mix evenly. The present application has no particular restrictions on the above-mentioned "mass ratio", as long as the purpose of the present application can be achieved. The present application has no restrictions on the type of sodium salt, as long as the purpose of the present application can be achieved. For example, sodium salt can include sodium hexafluorophosphate (NaPF 6 ), sodium perchlorate (NaClO 4 ), sodium tetraphenylborate [NaB(C 6 H 5 ) 4 ], sodium trifluoromethanesulfonate (NaCF 3 SO 3 ), sodium fluorosilicate (NaSiF 6 ), sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), sodium dioxalate borate (NaBOB) or sodium difluorooxalate borate (NaDFOB). The present application has no particular limitation on the concentration of the sodium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, the concentration of the sodium salt is 1.0 mol / L to 2.0 mol / L.
[0046] Example
[0047] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods.
[0048] Test methods and equipment:
[0049] Scanning electron microscope test of cathode precursor material and cathode material:
[0050] After grinding the positive electrode precursor material and the positive electrode material, they are tested by a scanning electron microscope (SEM). The instrument's focused electron beam is used to excite the sample surface to generate secondary electrons, backscattered electrons, characteristic X-rays and other secondary information, and these secondary information are collected and detected for the microscopic morphology of the material surface. The test conditions of SEM are: working distance 10mm to 30mm, objective lens aperture 50μm to 500μm, acceleration voltage 10kV to 20kV, and the test instrument model is Hitachi S3400.
[0051] Cathode precursor material particle size and particle size distribution width test:
[0052] The particle size test method refers to GB / T 19077-2016. The Dv10, Dv50 and Dv90 of the positive electrode precursor material of the sodium ion battery are tested using a laser particle size analyzer. During the test, when the laser beam passes through the dispersed particle sample, the particle size measurement is completed by measuring the intensity of the scattered light. The refractive index of the particles used in the test is 2.61. One sample is tested three times, and the particle size is finally measured by taking the average value of the three tests to measure Dv10, Dv50 and Dv90 respectively. Laser particle size analyzer model: FBS-1570ZXP, test range 0.1μm to 500μm.
[0053] The particle size distribution width K90 of the positive electrode precursor material is (Dv90-Dv10) / Dv50. Among them, the above Dv50 represents the particle size of the material in the volume-based particle size distribution, from the small particle size side, reaching 50% of the volume accumulation; the above Dv10 represents the particle size of the material in the volume-based particle size distribution, from the small particle size side, reaching 10% of the volume accumulation; the above Dv90 represents the particle size of the material in the volume-based particle size distribution, from the small particle size side, reaching 90% of the volume accumulation.
[0054] Cathode material XRD test:
[0055] The positive electrode materials prepared in each embodiment and each comparative example were ground and transferred to a glass slide stage, and then transferred to an X-ray diffractometer (model: Shimadzu XRD-6000) for scanning testing. The test conditions were: scanning range of 10° to 80°, scanning speed of 5° / min, target material of Cu, tube current of 40 mA, and tube voltage of 40 kV.
[0056] Positive electrode precursor material tap density test:
[0057] The tap density tester is used to test the tap density of the positive electrode precursor material. The positive electrode precursor material in the steel cylinder is vibrated in the tap density tester for 20 minutes, and the volume after vibration is calculated by its descending depth, and then the tap density is obtained by dividing the weight of the positive electrode precursor material by its volume after vibration.
[0058] Cathode precursor material specific surface area test:
[0059] The specific surface area of the cathode precursor material is tested using a specific surface area analyzer. The sample is first heated and vacuumed to remove impurity gases adsorbed on the surface and then weighed. It is then placed in liquid nitrogen at liquid nitrogen temperature and the nitrogen adsorption of the sample is measured at different pre-set pressure points to obtain an adsorption isotherm. The data is then processed by a computer to calculate the specific surface area of the cathode precursor material from the adsorption isotherm.
[0060] Secondary battery 0.1C, 2-4V first charge and discharge specific capacity and cycle performance test:
[0061] The sodium ion secondary batteries in each embodiment and each comparative example were subjected to charge and discharge tests using a LAND series battery test system (LANDCT3002A): the batteries were charged at a constant current rate of 0.1C (1C = 150 mAh / g) at room temperature until the voltage reached 4V, and then charged at a constant voltage of 4V until the current was lower than 0.05C, so that they were in a 4V fully charged state, and then discharged at a constant current rate of 0.1C until the voltage reached 2V, and the obtained capacity was recorded as the 0.1C first discharge specific capacity.
[0062] The above steps were then repeated for 1000 charge and discharge cycles, and the discharge specific capacity of the 1000th cycle was recorded. Cycle capacity retention rate = (discharge specific capacity of the 1000th cycle / discharge specific capacity of the first cycle) × 100%.
[0063] Secondary battery 0.1C, 2.2-4.4V first charge and discharge specific capacity and cycle performance test:
[0064] The sodium ion secondary batteries in each embodiment and each comparative example were subjected to charge and discharge tests using a LAND series battery test system (LANDCT3002A): the batteries were charged at a constant current rate of 0.1C (1C = 170 mAh / g) at room temperature until the voltage reached 4.4V, and then charged at a constant voltage of 4.4V until the current was less than 0.05C, so that the batteries were in a fully charged state of 4.4V, and then discharged at a constant current rate of 0.1C until the voltage reached 2.2V. The capacity obtained was recorded as the 0.1C first discharge specific capacity.
[0065] The above steps were then repeated for 300 charge and discharge cycles, and the discharge specific capacity at the 300th cycle was recorded. Cycle capacity retention rate = (discharge specific capacity at the 300th cycle / discharge specific capacity at the first cycle) × 100%.
[0066] Example 1
[0067] <Preparation of positive electrode precursor materials>
[0068] (1) According to the positive electrode precursor material Mn 0.38 Fe 0.15 Ti 0.07 Ni 0.34 Li 0.06 CO 3 The stoichiometric ratios of manganese, iron, titanium, nickel and lithium in the mixture were calculated by weighing 0.38 mol manganese acetate [Mn(CH 3 COO 2 ], 0.15 mol ferric chloride (FeCl3), 0.07 mol titanyl sulfate (TiOSO4), 0.34 mol nickel acetate [Ni(CH3 COO 2 ] and 0.06 mol lithium acetate (CH 3 COOLi) was dissolved in deionized water to prepare a mixed metal salt solution with a total concentration of 1.7 mol / L of manganese, iron, titanium, nickel and lithium;
[0069] (2) adding deionized water as a base liquid to a coprecipitation reaction vessel, and then introducing nitrogen into the base liquid at a nitrogen flow rate of 35 mL / min, and then dropping a 1 mol / L sodium carbonate solution, a 0.5 mol / L ammonia solution and the mixed metal salt solution into the coprecipitation reaction vessel to perform a coprecipitation reaction. During the coprecipitation reaction, the pH in the coprecipitation reaction vessel was controlled to be 8.5, the reaction temperature was 55° C., and the stirring speed was 650 r / min;
[0070] (3) After the injection of the mixed metal salt solution in the coprecipitation reaction container is completed, the addition of the precipitant and the complexing agent is stopped, and then the stirring is continued at a stirring speed of 260 r / min, and the aging reaction is carried out for 8 hours. Then, the obtained coprecipitation product is filtered and washed with deionized water, and then placed in a vacuum drying oven at 100° C. for 18 hours to obtain the positive electrode precursor material Mn 0.38 Fe 0.15 Ti 0.07 Ni 0.34 Li 0.06 CO 3 The Dv50 of the cathode precursor material is 5 μm, the K90 is 0.76, and the tap density of the cathode precursor material is 1.5 g / cm 3 , specific surface area is 20m 2 / g.
[0071] <Preparation of positive electrode material>
[0072] (1) According to the positive electrode material Na 0.95 Mn 0.38 Fe 0.15 Ti 0.07 Ni 0.34 Li 0.06 O 2 The stoichiometric ratio of sodium element to positive electrode precursor material is as follows: 0.5 mol sodium carbonate (Na 2 CO 3 ) and 1 mol of the positive electrode precursor material Mn prepared above 0.38 Fe 0.15 Ti 0.07 Ni 0.34 Li 0.06 CO 3The mixture was placed in a ball mill for ball milling, wherein the ball mill speed was 400 rpm and the ball milling time was 5 hours to obtain a mixture; wherein, when weighing the sodium source, an additional 5 mol% excess was added on the basis of the original molar amount of the sodium element to appropriately supplement the sodium element loss during the high-temperature sintering process.
[0073] (2) heating the obtained mixture to 950°C at a first stage heating rate of 4°C / min and keeping the temperature for 10 hours under an oxygen atmosphere, and then heating the mixture to 1030°C at a second stage heating rate of 4°C / min and keeping the temperature for 12 hours; then cooling the mixture to room temperature at a natural cooling rate to obtain the sodium ion battery positive electrode material Na 0.95 Mn 0.38 Fe 0.15 Ti 0.07 Ni 0.34 Li 0.06 O 2 .
[0074] <Preparation of positive electrode sheet>
[0075] The positive electrode material, polyvinylidene fluoride (PVDF) and conductive carbon black (SP) prepared above are mixed in a mass ratio of 80:10:10, and N-methylpyrrolidone (NMP) is added as a solvent. After stirring evenly, it is coated on one surface of the positive electrode current collector aluminum foil, and then placed in a 70°C forced air oven for forced air drying for 1 hour, and then placed in a vacuum oven at 80°C for vacuum drying for 24 hours, and finally punched out with a button battery slicer equipped with a 12 mm diameter punching die to obtain a positive electrode sheet.
[0076] <Preparation of Electrolyte>
[0077] In a glove box protected by inert argon gas and with water and oxygen content <0.1ppm, 1 mol / L sodium hexafluorophosphate (NaPF 6 ) is dissolved in an organic solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 and mixed evenly to obtain an electrolyte.
[0078] <Preparation of Separator>
[0079] A porous polypropylene film with a thickness of 16 μm was used.
[0080] <Preparation of Sodium Ion Batteries>
[0081] In a glove box protected by argon gas and with water and oxygen content <0.1ppm, button cells were assembled in the order of negative electrode shell, metallic sodium sheet (thickness 0.5mm, diameter 14mm, analytical grade), electrolyte, diaphragm, electrolyte, positive electrode sheet, gasket, spring sheet, and positive electrode shell. Finally, they were packaged using a button cell packaging machine to obtain the CR2032 button sodium ion battery used in the test.
[0082] Example 2
[0083] <Preparation of positive electrode precursor materials>
[0084] (1) According to the positive electrode precursor material Mn 0.33 Fe 0.2 Ti 0.07 Ni 0.34 Li 0.06 CO 3 The stoichiometric ratios of manganese, iron, titanium, nickel and lithium in the mixture were calculated by weighing 0.33 mol manganese acetate [Mn(CH 3 COO 2 ], 0.2 mol ferric chloride (FeCl3), 0.07 mol titanyl sulfate (TiOSO4), 0.34 mol nickel acetate [Ni(CH 3 COO 2 ] and 0.06 mol lithium acetate (CH 3 COOLi) was dissolved in deionized water to prepare a mixed metal salt solution with a total concentration of 1.7 mol / L of manganese, iron, titanium, nickel and lithium;
[0085] (2) adding deionized water as a base liquid to a coprecipitation reaction vessel, and then introducing nitrogen into the base liquid at a nitrogen flow rate of 35 mL / min, and then dropping a 1 mol / L sodium carbonate solution, a 0.5 mol / L ammonia solution and the mixed metal salt solution into the coprecipitation reaction vessel to perform a coprecipitation reaction. During the coprecipitation reaction, the pH in the coprecipitation reaction vessel was controlled to be 8.5, the reaction temperature was 55° C., and the stirring speed was 650 r / min;
[0086] (3) After the injection of the mixed metal salt solution in the coprecipitation reaction container is completed, the addition of the precipitant and the complexing agent is stopped, and then the stirring is continued at a stirring speed of 260 r / min, and the aging reaction is carried out for 8 hours. Then, the obtained coprecipitation product is filtered and washed with deionized water, and then placed in a vacuum drying oven at 100° C. for 18 hours to obtain the positive electrode precursor material Mn 0.33 Fe 0.2 Ti 0.07 Ni 0.34 Li 0.06 CO 3 The Dv50 of the cathode precursor material is 5 μm, the K90 is 0.76, and the tap density of the cathode precursor material is 1.5 g / cm 3 , specific surface area is 20m 2 / g.
[0087] The rest are the same as in Example 1.
[0088] Example 3
[0089] <Preparation of positive electrode precursor materials>
[0090] (1) According to the positive electrode precursor material Mn 0.43 Fe 0.1 Ti 0.07 Ni 0.34 Li 0.06 CO 3 The stoichiometric ratios of manganese, iron, titanium, nickel and lithium in the mixture were calculated by weighing 0.43 mol manganese acetate [Mn(CH 3 COO 2 ], 0.1 mol ferric chloride (FeCl3), 0.07 mol titanyl sulfate (TiOSO4), 0.34 mol nickel acetate [Ni(CH 3 COO 2 ] and 0.06 mol lithium acetate (CH 3 COOLi) was dissolved in deionized water to prepare a mixed metal salt solution with a total concentration of 1.7 mol / L of manganese, iron, titanium, nickel and lithium;
[0091] (2) adding deionized water as a base liquid to a coprecipitation reaction vessel, and then introducing nitrogen into the base liquid at a nitrogen flow rate of 35 mL / min, and then dropping a 1 mol / L sodium carbonate solution, a 0.5 mol / L ammonia solution and the mixed metal salt solution into the coprecipitation reaction vessel to perform a coprecipitation reaction. During the coprecipitation reaction, the pH in the coprecipitation reaction vessel was controlled to be 8.5, the reaction temperature was 55° C., and the stirring speed was 650 r / min;
[0092] (3) After the injection of the mixed metal salt solution in the coprecipitation reaction container is completed, the addition of the precipitant and the complexing agent is stopped, and then the stirring is continued at a stirring speed of 260 r / min, and the aging reaction is carried out for 8 hours. Then, the obtained coprecipitation product is filtered and washed with deionized water, and then placed in a vacuum drying oven at 100° C. for 18 hours to obtain the positive electrode precursor material Mn 0.43 Fe 0.1 Ti 0.07 Ni 0.34 Li 0.06 CO 3 The Dv50 of the cathode precursor material is 5 μm, the K90 is 0.76, and the tap density of the cathode precursor material is 1.5 g / cm 3 , specific surface area is 20m 2 / g.
[0093] The rest are the same as in Example 1.
[0094] Example 4
[0095] <Preparation of positive electrode precursor materials>
[0096] (1) According to the positive electrode precursor material Mn 0.25 Fe 0.2 Ti 0.15 Ni 0.3 Li 0.1 CO 3 The stoichiometric ratios of manganese, iron, titanium, nickel and lithium in the mixture were calculated by weighing 0.25 mol manganese acetate [Mn(CH 3 COO 2 ], 0.2 mol ferric chloride (FeCl3), 0.15 mol titanyl sulfate (TiOSO4), 0.3 mol nickel acetate [Ni(CH 3 COO 2 ] and 0.1 mol lithium acetate (CH 3 COOLi) was dissolved in deionized water to prepare a mixed metal salt solution with a total concentration of 1.7 mol / L of manganese, iron, titanium, nickel and lithium;
[0097] (2) adding deionized water as a base liquid to a coprecipitation reaction vessel, and then introducing nitrogen into the base liquid at a nitrogen flow rate of 35 mL / min, and then dropping a 1 mol / L sodium carbonate solution, a 0.5 mol / L ammonia solution and the mixed metal salt solution into the coprecipitation reaction vessel to perform a coprecipitation reaction. During the coprecipitation reaction, the pH in the coprecipitation reaction vessel was controlled to be 8.5, the reaction temperature was 55° C., and the stirring speed was 650 r / min;
[0098] (3) After the injection of the mixed metal salt solution in the coprecipitation reaction container is completed, the addition of the precipitant and the complexing agent is stopped, and then the stirring is continued at a stirring speed of 260 r / min, and the aging reaction is carried out for 8 hours. Then, the obtained coprecipitation product is filtered and washed with deionized water, and then placed in a vacuum drying oven at 100° C. for 18 hours to obtain the positive electrode precursor material Mn 0.25 Fe 0.2 Ti 0.15 Ni 0.3 Li 0.1 CO 3 The Dv50 of the cathode precursor material is 5 μm, the K90 is 0.76, and the tap density of the cathode precursor material is 1.5 g / cm 3 , specific surface area is 20m 2 / g.
[0099] The rest are the same as in Example 1.
[0100] Example 5
[0101] <Preparation of positive electrode precursor materials>
[0102] (1) According to the positive electrode precursor material Mn 0.42 Fe 0.15 Ti 0.03 Ni 0.34 Li 0.06 CO 3 The stoichiometric ratios of manganese, iron, titanium, nickel and lithium in the mixture were calculated by weighing 0.42 mol manganese acetate [Mn(CH 3 COO 2 ], 0.15 mol ferric chloride (FeCl3), 0.03 mol titanyl sulfate (TiOSO4), 0.34 mol nickel acetate [Ni(CH 3 COO 2 ] and 0.06 mol lithium acetate (CH 3 COOLi) was dissolved in deionized water to prepare a mixed metal salt solution with a total concentration of 1.7 mol / L of manganese, iron, titanium, nickel and lithium;
[0103] (2) adding deionized water as a base liquid to a coprecipitation reaction vessel, and then introducing nitrogen into the base liquid at a nitrogen flow rate of 35 mL / min, and then dropping a 1 mol / L sodium carbonate solution, a 0.5 mol / L ammonia solution and the mixed metal salt solution into the coprecipitation reaction vessel to perform a coprecipitation reaction. During the coprecipitation reaction, the pH in the coprecipitation reaction vessel was controlled to be 8.5, the reaction temperature was 55° C., and the stirring speed was 650 r / min;
[0104] (3) After the injection of the mixed metal salt solution in the coprecipitation reaction container is completed, the addition of the precipitant and the complexing agent is stopped, and then the stirring is continued at a stirring speed of 260 r / min, and the aging reaction is carried out for 8 hours. Then, the obtained coprecipitation product is filtered and washed with deionized water, and then placed in a vacuum drying oven at 100° C. for 18 hours to obtain the positive electrode precursor material Mn 0.42 Fe 0.15 Ti 0.03 Ni 0.34 Li 0.06 CO 3 The Dv50 of the cathode precursor material is 5 μm, the K90 is 0.76, and the tap density of the cathode precursor material is 1.5 g / cm 3 , specific surface area is 20m 2 / g.
[0105] The rest are the same as in Example 1.
[0106] Example 6
[0107] <Preparation of positive electrode precursor materials>
[0108] (1) According to the positive electrode precursor material Mn 0.38 Fe 0.15 Ti 0.07 Ni 0.3 Li 0.1 CO 3 The stoichiometric ratios of manganese, iron, titanium, nickel and lithium in the mixture were calculated by weighing 0.38 mol manganese acetate [Mn(CH 3 COO 2 ], 0.15 mol ferric chloride (FeCl3), 0.07 mol titanyl sulfate (TiOSO4), 0.3 mol nickel acetate [Ni(CH 3 COO 2 ] and 0.1 mol lithium acetate (CH 3 COOLi) was dissolved in deionized water to prepare a mixed metal salt solution with a total concentration of 1.7 mol / L of manganese, iron, titanium, nickel and lithium;
[0109] (2) adding deionized water as a base liquid to a coprecipitation reaction vessel, and then introducing nitrogen into the base liquid at a nitrogen flow rate of 35 mL / min, and then dropping a 1 mol / L sodium carbonate solution, a 0.5 mol / L ammonia solution and the mixed metal salt solution into the coprecipitation reaction vessel to perform a coprecipitation reaction. During the coprecipitation reaction, the pH in the coprecipitation reaction vessel was controlled to be 8.5, the reaction temperature was 55° C., and the stirring speed was 650 r / min;
[0110] (3) After the injection of the mixed metal salt solution in the coprecipitation reaction container is completed, the addition of the precipitant and the complexing agent is stopped, and then the stirring is continued at a stirring speed of 260 r / min, and the aging reaction is carried out for 8 hours. Then, the obtained coprecipitation product is filtered and washed with deionized water, and then placed in a vacuum drying oven at 100° C. for 18 hours to obtain the positive electrode precursor material Mn 0.38 Fe 0.15 Ti 0.07 Ni 0.3 Li 0.1 CO 3 The Dv50 of the cathode precursor material is 5 μm, the K90 is 0.76, and the tap density of the cathode precursor material is 1.5 g / cm 3 , specific surface area is 20m 2 / g.
[0111] The rest are the same as in Example 1.
[0112] Example 7
[0113] <Preparation of positive electrode precursor materials>
[0114] (1) According to the positive electrode precursor material Mn 0.38 Fe 0.15 Ti 0.07 Ni 0.38 Li 0.02 CO 3 The stoichiometric ratios of manganese, iron, titanium, nickel and lithium in the mixture were calculated by weighing 0.38 mol manganese acetate [Mn(CH 3 COO 2 ], 0.15 mol ferric chloride (FeCl3), 0.07 mol titanyl sulfate (TiOSO4), 0.38 mol nickel acetate [Ni(CH 3 COO 2 ] and 0.02 mol lithium acetate (CH 3 COOLi) was dissolved in deionized water to prepare a mixed metal salt solution with a total concentration of 1.7 mol / L of manganese, iron, titanium, nickel and lithium;
[0115] (2) adding deionized water as a base liquid to a coprecipitation reaction vessel, and then introducing nitrogen into the base liquid at a nitrogen flow rate of 35 mL / min, and then dropping a 1 mol / L sodium carbonate solution, a 0.5 mol / L ammonia solution and the mixed metal salt solution into the coprecipitation reaction vessel to perform a coprecipitation reaction. During the coprecipitation reaction, the pH in the coprecipitation reaction vessel was controlled to be 8.5, the reaction temperature was 55° C., and the stirring speed was 650 r / min;
[0116] (3) After the injection of the mixed metal salt solution in the coprecipitation reaction container is completed, the addition of the precipitant and the complexing agent is stopped, and then the stirring is continued at a stirring speed of 260 r / min, and the aging reaction is carried out for 8 hours. Then, the obtained coprecipitation product is filtered and washed with deionized water, and then placed in a vacuum drying oven at 100° C. for 18 hours to obtain the positive electrode precursor material Mn 0.38 Fe 0.15 Ti 0.07 Ni 0.38 Li 0.02 CO 3 The Dv50 of the cathode precursor material is 5 μm, the K90 is 0.76, and the tap density of the cathode precursor material is 1.5 g / cm 3 , specific surface area is 20m 2 / g.
[0117] The rest are the same as in Example 1.
[0118] Example 8
[0119] <Preparation of positive electrode precursor materials>
[0120] (1) According to the positive electrode precursor material Mn0.25 Fe 0.2 Ti 0.15 Ni 0.3 Li 0.1 CO 3 The stoichiometric ratios of manganese, iron, titanium, nickel and lithium in the mixture were calculated by weighing 0.25 mol manganese acetate [Mn(CH 3 COO 2 ], 0.2 mol ferric chloride (FeCl3), 0.15 mol titanyl sulfate (TiOSO4), 0.3 mol nickel acetate [Ni(CH 3 COO 2 ] and 0.1 mol lithium acetate (CH 3 COOLi) was dissolved in deionized water to prepare a mixed metal salt solution with a total concentration of 1.7 mol / L of manganese, iron, titanium, nickel and lithium;
[0121] (2) adding deionized water as a base liquid to a coprecipitation reaction vessel, and then introducing nitrogen into the base liquid at a nitrogen flow rate of 35 mL / min, and then dropping a 1 mol / L sodium carbonate solution, a 0.5 mol / L ammonia solution and the mixed metal salt solution into the coprecipitation reaction vessel to perform a coprecipitation reaction. During the coprecipitation reaction, the pH in the coprecipitation reaction vessel was controlled to be 8.5, the reaction temperature was 55° C., and the stirring speed was 650 r / min;
[0122] (3) After the injection of the mixed metal salt solution in the coprecipitation reaction container is completed, the addition of the precipitant and the complexing agent is stopped, and then the stirring is continued at a stirring speed of 260 r / min, and the aging reaction is carried out for 8 hours. Then, the obtained coprecipitation product is filtered and washed with deionized water, and then placed in a vacuum drying oven at 100° C. for 18 hours to obtain the positive electrode precursor material Mn 0.25 Fe 0.2 Ti 0.15 Ni 0.3 Li 0.1 CO 3 The Dv50 of the cathode precursor material is 5 μm, the K90 is 0.76, and the tap density of the cathode precursor material is 1.5 g / cm 3 , specific surface area is 20m 2 / g.
[0123] The rest are the same as in Example 1.
[0124] Example 9
[0125] <Preparation of positive electrode precursor materials>
[0126] (1) According to the positive electrode precursor material Mn 0.47 Fe0.1 Ti 0.03 Ni 0.38 Li 0.02 CO 3 The stoichiometric ratios of manganese, iron, titanium, nickel and lithium in the mixture were calculated by weighing 0.47 mol manganese acetate [Mn(CH 3 COO 2 ], 0.1 mol ferric chloride (FeCl3), 0.03 mol titanyl sulfate (TiOSO4), 0.38 mol nickel acetate [Ni(CH 3 COO 2 ] and 0.02 mol lithium acetate (CH 3 COOLi) was dissolved in deionized water to prepare a mixed metal salt solution with a total concentration of 1.7 mol / L of manganese, iron, titanium, nickel and lithium;
[0127] (2) adding deionized water as a base liquid to a coprecipitation reaction vessel, and then introducing nitrogen into the base liquid at a nitrogen flow rate of 35 mL / min, and then dropping a 1 mol / L sodium carbonate solution, a 0.5 mol / L ammonia solution and the mixed metal salt solution into the coprecipitation reaction vessel to perform a coprecipitation reaction. During the coprecipitation reaction, the pH in the coprecipitation reaction vessel was controlled to be 8.5, the reaction temperature was 55° C., and the stirring speed was 650 r / min;
[0128] (3) After the injection of the mixed metal salt solution in the coprecipitation reaction container is completed, the addition of the precipitant and the complexing agent is stopped, and then the stirring is continued at a stirring speed of 260 r / min, and the aging reaction is carried out for 8 hours. Then, the obtained coprecipitation product is filtered and washed with deionized water, and then placed in a vacuum drying oven at 100° C. for 18 hours to obtain the positive electrode precursor material Mn 0.47 Fe 0.1 Ti 0.03 Ni 0.38 Li 0.02 CO 3 The Dv50 of the cathode precursor material is 5 μm, the K90 is 0.76, and the tap density of the cathode precursor material is 1.5 g / cm 3 , specific surface area is 20m 2 / g.
[0129] The rest are the same as in Example 1.
[0130] Example 10
[0131] <Preparation of positive electrode material>
[0132] (1) According to the positive electrode material NaMn 0.38 Fe 0.15 Ti 0.07Ni 0.34 Li 0.06 O 2 The stoichiometric ratio of sodium element to positive electrode precursor material is as follows: 0.525 mol sodium carbonate (Na 2 CO 3 ) and 1 mol of positive electrode precursor material Mn 0.38 Fe 0.15 Ti 0.07 Ni 0.34 Li 0.06 CO 3 The mixture was placed in a ball mill for ball milling, wherein the ball mill speed was 400 rpm and the ball milling time was 5 hours to obtain a mixture; wherein, when weighing the sodium source, an additional 5 mol% excess was added on the basis of the original molar amount of the sodium element to appropriately supplement the sodium element loss during the high-temperature sintering process.
[0133] (2) The obtained mixture is heated to 950°C at a first stage heating rate of 4°C / min under an oxygen atmosphere and kept at this temperature for 10 hours, and then heated to 1030°C at a second stage heating rate of 4°C / min and kept at this temperature for 12 hours; and then cooled to room temperature at a natural cooling rate to obtain the sodium ion battery positive electrode material NaMn 0.38 Fe 0.15 Ti 0.07 Ni 0.34 Li 0.06 O 2 .
[0134] The rest are the same as in Example 1.
[0135] Embodiment 11
[0136] <Preparation of positive electrode material>
[0137] (1) According to the positive electrode material Na 0.85 Mn 0.38 Fe 0.15 Ti 0.07 Ni 0.34 Li 0.06 O 2 The stoichiometric ratio of sodium element to positive electrode precursor material is 0.446 mol sodium carbonate (Na 2 CO 3 ) and 1 mol of the positive electrode precursor material Mn prepared above 0.38 Fe 0.15 Ti 0.07 Ni 0.34 Li 0.06 CO 3The mixture was placed in a ball mill for ball milling, wherein the ball mill speed was 400 rpm and the ball milling time was 5 hours to obtain a mixture; wherein, when weighing the sodium source, an additional 5 mol% excess was added on the basis of the original molar amount of the sodium element to appropriately supplement the sodium element loss during the high-temperature sintering process.
[0138] (2) heating the obtained mixture to 950°C at a first stage heating rate of 4°C / min and keeping the temperature for 10 hours under an oxygen atmosphere, and then heating the mixture to 1030°C at a second stage heating rate of 4°C / min and keeping the temperature for 12 hours; then cooling the mixture to room temperature at a natural cooling rate to obtain the sodium ion battery positive electrode material Na 0.85 Mn 0.38 Fe 0.15 Ti 0.07 Ni 0.34 Li 0.06 O 2 .
[0139] The rest are the same as in Example 1.
[0140] Example 12
[0141] Except that in <Preparation of Positive Electrode Precursor Material>, step (1) is adjusted to "a mixed metal salt solution with a total concentration of manganese, iron, titanium, nickel and lithium of 2 mol / L" as shown in Table 2, thereby adjusting the Dv50 of the positive electrode precursor material to 3 μm as shown in Table 1, the rest is the same as Example 1.
[0142] Embodiment 13
[0143] Except that in <Preparation of Positive Electrode Precursor Material>, step (1) is adjusted to "a mixed metal salt solution with a total concentration of manganese, iron, titanium, nickel and lithium of 1.2 mol / L" as shown in Table 2, thereby adjusting the Dv50 of the positive electrode precursor material to 7 μm as shown in Table 1, the rest is the same as Example 1.
[0144] Embodiment 14
[0145] In addition to the step (2) in <Preparation of positive electrode precursor material>, as shown in Table 2, the nitrogen flow rate is 20 mL / min, and then 1 mol / L sodium carbonate solution, 0.5 mol / L ammonia solution and the mixed metal salt solution are respectively added dropwise into the coprecipitation reaction container for coprecipitation reaction, and during the coprecipitation reaction, the pH in the coprecipitation reaction container is controlled to be 7.5, the reaction temperature is 50°C, and the stirring speed is 500 r / min. The tap density of the positive electrode precursor material is regulated to be 1.3 g / cm as shown in Table 1. 3 Except for this, the rest are the same as in Example 1.
[0146] Embodiment 15
[0147] In addition to the step (2) in <Preparation of positive electrode precursor material>, as shown in Table 2, the nitrogen flow rate is 50 mL / min, and then 1 mol / L sodium carbonate solution, 0.5 mol / L ammonia solution and the mixed metal salt solution are respectively added dropwise into the coprecipitation reaction container for coprecipitation reaction, and during the coprecipitation reaction, the pH in the coprecipitation reaction container is controlled to be 9.5, the reaction temperature is 60°C, and the stirring speed is 800 r / min. The tap density of the positive electrode precursor material is regulated to be 1.8 g / cm as shown in Table 1. 3 Except for this, the rest are the same as those in Example 1.
[0148] Example 16
[0149] Except that in <Preparation of positive electrode precursor material>, as shown in Table 2, step (3) is regulated to "continue stirring at a stirring speed of 200 r / min, perform aging reaction for 6 h, and then filter and wash the obtained coprecipitated product with deionized water, and then place it in a vacuum drying oven at 80°C for 12 h", so as to regulate the specific surface area of the positive electrode precursor material to 25 m 2 Except for the above, the rest are the same as those in Example 1.
[0150] Embodiment 17
[0151] Except that in <Preparation of positive electrode precursor material>, as shown in Table 2, step (3) is regulated to "continue stirring at a stirring speed of 300 r / min, perform aging reaction for 10 h, and then filter and wash the obtained coprecipitated product with deionized water, and then place it in a vacuum drying oven at 120°C for 24 h", so as to regulate the specific surface area of the positive electrode precursor material to 15 m 2 Except for the above, the rest are the same as those in Example 1.
[0152] Example 18 to Example 19
[0153] Except that in <Preparation of Positive Electrode Precursor Material>, the types of raw materials of each element are regulated as shown in Table 1, the rest are the same as Example 1.
[0154] Comparative Example 1
[0155] In addition to the step (1) of "preparation of positive electrode precursor material" as shown in Table 1, the control step (1) is "according to the positive electrode precursor material Mn 0.58 Fe 0.01 Ti 0.01 Ni 0.39 Li 0.01 CO 3 The stoichiometric ratios of manganese, iron, titanium, nickel and lithium in the mixture were calculated by weighing 0.58 mol manganese acetate [Mn(CH3 COO 2 ], 0.01 mol ferric chloride (FeCl3), 0.01 mol titanyl sulfate (TiOSO4), 0.39 mol nickel acetate [Ni(CH 3 COO 2 ] and 0.01 mol lithium acetate (CH 3 COOLi) was dissolved in deionized water to prepare a mixed metal salt solution with a total concentration of manganese, iron, titanium, nickel and lithium of 1.7 mol / L, and the rest was the same as Example 1.
[0156] Comparative Example 2
[0157] <Preparation of positive electrode precursor materials>
[0158] (1) According to the positive electrode precursor material Mn 0.15 Fe 0.25 Ti 0.2 Ni 0.25 Li 0.15 CO 3 The stoichiometric ratios of manganese, iron, titanium, nickel and lithium in the mixture were calculated by weighing 0.15 mol manganese acetate [Mn(CH 3 COO 2 ]、0.25mol ferric chloride (FeCl 3 ), 0.2 mol titanyl sulfate (TiOSO 4 ), 0.25 mol nickel acetate [Ni(CH 3 COO 2 ] and 0.15 mol lithium acetate (CH 3 COOLi) was dissolved in deionized water to prepare a mixed metal salt solution with a total concentration of 1.7 mol / L of manganese, iron, titanium, nickel and lithium;
[0159] (2) adding deionized water as a base liquid to a coprecipitation reaction vessel, and then introducing nitrogen into the base liquid at a nitrogen flow rate of 35 mL / min, and then dropping a 1 mol / L sodium carbonate solution, a 0.5 mol / L ammonia solution and the mixed metal salt solution into the coprecipitation reaction vessel to perform a coprecipitation reaction. During the coprecipitation reaction, the pH in the coprecipitation reaction vessel was controlled to be 8.5, the reaction temperature was 55° C., and the stirring speed was 650 r / min;
[0160] (3) After the injection of the mixed metal salt solution in the coprecipitation reaction container is completed, the addition of the precipitant and the complexing agent is stopped, and then the stirring is continued at a stirring speed of 260 r / min, and the aging reaction is carried out for 8 hours. Then, the obtained coprecipitation product is filtered and washed with deionized water, and then placed in a vacuum drying oven at 100° C. for 18 hours to obtain the positive electrode precursor material Mn0.15 Fe 0.25 Ti 0.2 Ni 0.25 Li 0.15 CO 3 The Dv50 of the cathode precursor material is 5 μm, the K90 is 2, and the tap density of the cathode precursor material is 1.5 g / cm 3 , specific surface area is 20m 2 / g.
[0161] The rest are the same as in Example 1.
[0162] Comparative Example 3
[0163] Except that in <Preparation of Positive Electrode Precursor Material>, step (1) is adjusted to "a mixed metal salt solution with a total concentration of manganese, iron, titanium, nickel and lithium of 3 mol / L" as shown in Table 2, thereby adjusting the Dv50 of the positive electrode precursor material to 1 μm as shown in Table 1, the rest is the same as Example 1.
[0164] Comparative Example 4
[0165] Except that in <Preparation of Positive Electrode Precursor Material>, step (1) is adjusted to "a mixed metal salt solution with a total concentration of manganese, iron, titanium, nickel and lithium of 0.5 mol / L" as shown in Table 2, thereby adjusting the Dv50 of the positive electrode precursor material to 10 μm as shown in Table 1, the rest is the same as Example 1.
[0166] Table 1
[0167]
[0168]
[0169] Table 2
[0170]
[0171]
[0172] Table 3
[0173]
[0174] Referring to Tables 1 to 3, it can be seen from Examples 1 to 19 and Comparative Examples 1 to 4 that the sodium ion battery positive electrode precursor material prepared by the coprecipitation method in the present application, by regulating the particle size, particle size distribution width and stoichiometric ratio of the positive electrode precursor material, the three doping elements produce a synergistic co-doping effect at different sites in the transition metal layer of the positive electrode material, thereby inhibiting the complex phase change of the layered oxide during the charge and discharge cycle, reducing the adverse effects of side reactions under high voltage, and making the positive electrode material have better structural stability and higher capacity density; by regulating the volume average particle size Dv50 of the positive electrode precursor material to 3μm to 7μm, the particle size distribution width K90≤0.9, the particle size of the positive electrode material is more uniform, thereby achieving better cycle stability.
[0175] Specifically, Figure 1 This is a scanning electron microscope image of the positive electrode precursor material in Example 1 of the present application, Figure 2 This is a scanning electron microscope image of the positive electrode precursor material in Comparative Example 2 of the present application. Figure 1 and Figure 2 It can be seen that the positive electrode precursor material in Example 1 has a good degree of molding and a more uniform particle size, while the positive electrode precursor material in Comparative Example 2 has a poor degree of molding and an uneven particle size, indicating that by adjusting the ratio of each element in the positive electrode precursor material to meet the following requirements: Mn 0.6-a-b Fe a Ti b Ni 0.4- c Li c CO 3 , 0.1≤a≤0.2, 0.03≤b≤0.15, 0.02≤c≤0.1, which is conducive to obtaining a positive electrode precursor material with more uniform particle size and better molding degree.
[0176] Figure 4 is the XRD spectrum of the positive electrode material in Example 1, Figure 5 is the XRD pattern of the positive electrode material in Comparative Example 2, from Figure 4 and Figure 5 It can be seen that the X-ray diffraction peak intensity of the positive electrode material prepared in Example 1 is significantly higher than that of the positive electrode material prepared in Comparative Example 2, indicating that by regulating the particle size, particle size distribution width and stoichiometric ratio of the positive electrode precursor material within the scope of this application, the obtained positive electrode material has higher crystallinity.
[0177] Figure 6 is a scanning electron microscope image of the positive electrode material in Example 1, from Figure 6 It can be seen that the overall structure of the positive electrode material is a relatively clear and complete block single crystal structure, with a regular and dense surface morphology and a relatively uniform size distribution; Figure 7This is a scanning electron microscope image of the positive electrode material in Comparative Example 1. Figure 7 It can be seen that there are obvious point-like impurities on the surface of the positive electrode material, and the size distribution is also relatively uneven, indicating that by adjusting the stoichiometric ratio of each component of the positive electrode precursor material within the scope of this application, it is beneficial to obtain a positive electrode material with uniform particles and good morphology.
[0178] Figure 8 The charge and discharge performance test diagram of the sodium ion battery in Example 1 at 0.1C and 2-4V is shown in FIG. Figure 8 It can be seen that the discharge capacity of the first cycle is 145 mAh / g, and the capacity retention rate after 1000 cycles is 91%, indicating that it has good cycle stability; Fig. 9 The charge and discharge performance test diagram of the sodium ion battery in Example 1 at 0.1C and 2.2-4.4V is shown in FIG. Fig. 9 It can be seen that the discharge specific capacity of the first cycle is 167 mAh / g, and the capacity retention rate after 300 cycles is 83%, indicating that it has good cycle stability and high voltage resistance.
[0179] It can be seen from Examples 1 to 9 and Comparative Examples 1 to 2 in Table 1 and Table 3 that by adjusting the ratio of each element in the positive electrode precursor material, the following conditions are met: Mn 0.6-a-b Fe a Ti b Ni 0.4-c Li c CO 3 , 0.1≤a≤0.2, 0.03≤b≤0.15, 0.02≤c≤0.1, which is conducive to obtaining a positive electrode material with good cycle stability and high capacity density.
[0180] It can be seen from Example 1, Example 10 and Example 11 in Table 1 and Table 3 that the present application adjusts the stoichiometric ratio of the sodium element to the precursor in the positive electrode material within the scope of the present application, so that the positive electrode material has a sufficiently high sodium content, which is also beneficial to the stability of the positive electrode material structure after the sodium ions are released, thereby making the positive electrode material have good cycle stability and high capacity density.
[0181] It can be seen from Example 1, Example 12 to Example 13, and Comparative Example 3 to Comparative Example 4 in Tables 1 to 3 that by adjusting the volume average particle size Dv50 of the positive electrode precursor material of the sodium ion battery to 3 μm to 7 μm and the particle size distribution width K90 ≤ 0.9, it is beneficial to improve the capacity density and cycle stability of the positive electrode material. Specifically, Figure 3 This is a particle size test diagram of the positive electrode precursor material in Example 1 of the present application, from Figure 3It can be seen that the volume average particle size Dv10 of the positive electrode precursor material in Example 1 is 3.5μm, Dv50 is 5μm, Dv90 is 7.3μm, and K90 is 0.76, indicating that the positive electrode precursor material obtained by regulating the concentration of the mixed metal salt solution within the scope of this application has a smaller particle size distribution width and a more uniform particle size.
[0182] The nitrogen flow rate, coprecipitation reaction pH, reaction temperature, and stirring speed during the coprecipitation reaction usually affect the tap density of the positive electrode precursor material. It can be seen from Example 1, Example 14, and Example 15 in Tables 1 to 3 that by regulating the nitrogen flow rate, coprecipitation reaction pH, reaction temperature, and stirring speed during the precipitation reaction within the scope of this application, it is beneficial to obtain a positive electrode precursor material with a good tap density.
[0183] During the aging process, the aging time, stirring speed, vacuum drying temperature and time usually have an impact on the specific surface area of the positive electrode precursor material. It can be seen from Example 1, Example 16 and Example 17 in Tables 1 to 3 that by adjusting the aging time, stirring speed, vacuum drying temperature and time within the scope of this application, it is beneficial to obtain a positive electrode precursor material with a better specific surface area.
[0184] It can be seen from Example 1, Example 18 and Example 19 in Table 1 and Table 3 that the present application is beneficial to obtaining a positive electrode precursor material with good cycle performance and higher capacity density by regulating the types of raw materials of each element of the positive electrode precursor material within the scope of the present application.
[0185] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusions, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the statement "include..." does not exclude the presence of other identical elements in the process, method, article or device including the element.
[0186] The above are only preferred embodiments of the present application and are not intended to limit the protection scope of the present application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present application are included in the protection scope of the present application.
Claims
1. A sodium ion battery cathode precursor material, wherein: The chemical formula of the positive electrode precursor material is: Mn 0.6-a- b Fe a Ti b Ni 0.4-c Li c CO3, 0.1≤a≤0.2, 0.03≤b≤0.15, 0.02≤c≤0.1, the volume average particle size Dv50 of the positive electrode precursor material is 3μm to 7μm, and the particle size distribution width K90≤0.
9.
2. The positive electrode precursor material according to claim 1, wherein The tap density of the positive electrode precursor material is 1.3 g / cm 3 Up to 1.8g / cm 3 , with a specific surface area of 15m 2 / g to 25m 2 / g.
3. The positive electrode precursor material according to claim 1, wherein The manganese source of the positive electrode precursor material is selected from at least one of manganese acetate, manganese nitrate or manganese sulfate.
4. The positive electrode precursor material according to claim 1, wherein The iron source of the positive electrode precursor material is selected from at least one of ferric chloride, ferric nitrate or ferric sulfate.
5. The positive electrode precursor material according to claim 1, wherein The titanium source of the positive electrode precursor material is selected from at least one of titanyl sulfate and titanium tetrachloride.
6. The positive electrode precursor material according to claim 1, wherein The nickel source of the positive electrode precursor material is selected from at least one of nickel acetate, nickel nitrate or nickel sulfate.
7. The positive electrode precursor material according to claim 1, wherein The lithium source of the positive electrode precursor material is selected from at least one of lithium acetate, lithium hydroxide or lithium nitrate.
8. A method for preparing a positive electrode precursor material according to any one of claims 1 to 7, wherein: The method comprises: (1) According to the positive electrode precursor material Mn 0.6-a-b Fe a Ti b Ni 0.4-c Li c The stoichiometric ratio of manganese, iron, titanium, nickel and lithium in CO3 is: weigh manganese source, iron source, titanium source, nickel source and lithium source respectively and dissolve them in deionized water to prepare a mixed metal salt solution with a total concentration of manganese, iron, titanium, nickel and lithium of 1.2 mol / L to 2 mol / L, wherein 0.1≤a≤0.2, 0.03≤b≤0.15, 0.02≤c≤0.1; (2) adding deionized water as a base liquid into a coprecipitation reaction container, and then introducing nitrogen into the base liquid at a nitrogen flow rate of 20 mL / min to 50 mL / min, and then respectively adding a precipitant, a complexing agent and the mixed metal salt solution into the coprecipitation reaction container to perform a coprecipitation reaction, wherein during the coprecipitation reaction, the pH in the coprecipitation reaction container is controlled to be 7.5 to 9.5, the reaction temperature is 50° C. to 60° C., and the stirring speed is 500 r / min to 800 r / min. Wherein, the precipitant is 1 mol / L sodium carbonate solution, and the complexing agent is 0.5 mol / L ammonia solution; (3) After the injection of the mixed metal salt solution in the coprecipitation reaction container is completed, the addition of the precipitant and the complexing agent is stopped, and then the stirring speed is continued at 200 r / min to 300 r / min, and the aging reaction is carried out for 6 h to 10 h, and then the obtained coprecipitation product is filtered and washed with deionized water, and then placed in a vacuum drying oven at 80° C. to 120° C. for 12 h to 24 h to obtain the positive electrode precursor material Mn 0.6-a-b Fe a Ti b Ni 0.4-c Li c CO3.
9. A positive electrode material comprising the positive electrode precursor material according to any one of claims 1 to 7, wherein: The chemical formula of the positive electrode material is: Na x Mn 0.6-a-b Fe a Ti b Ni 0.4-c Li c O2, 0.85≤x≤1, 0.1≤a≤0.2, 0.03≤b≤0.15, 0.02≤c≤0.1, and the sodium source of the positive electrode material is selected from at least one of sodium carbonate, sodium bicarbonate or sodium nitrate.